Granulocyte colony stimulating factor in COS-IUI cycles - Shetty, Pradnya Devdas; Lad, Nikita; Vishwekar, Pallavi; Shivtare, Mamta Vijay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: An unresolved assisted reproductive technique problem is the unresponsive, thin endometrium. Approximately 0.6%-0.8% of patients do not reach the minimum thickness. Using endometrial co culture, G-CSF>130pg/mL was associated with significantly improved pregnancy rate in ART cycles. This is a retrospective study that included all unexplained infertility cycles with controlled ovulation stimulation –IUI protocols. Aim was to note the effects of G-CSF on thin endometrium and pregnancy rate in G-CSF administered COS-IUI cycles. Methods: This study was done in the IVF department of Dr D Y Patil University, Navi Mumbai, India. Thin endometrium was defined as ET<7mm on transvaginal ultrasound. Clomiphene citrate was used for ovulation induction in strengths of 100mg or 50mg on day 2 of their cycle based on the antral follicle count. Trigger used was injection 10,000µg urinary hCG. On the same day when the trigger injection was given, 300 units G-CSF was instilled into the uterus. Post 36 hours IUI was done under aseptic precautions .After 16 days β-hCG levels were done to determine whether there is a pregnancy. Results: In present study,200 COS-IUI cycles were analysed.50 cycles showed a thin endometrium and in them G-CSF was used. The chemical pregnancy rates was 32%, the intrauterine pregnancy rate was 28%, ectopic pregnancy rate was 4%. Conclusions: Present study concluded that G-CSF increases ET significantly in COS-IUI cycles in the event of thin endometrium. In view of small cohort size further larger randomized controlled trials may be required to substantiate the above conclusions.